Transnational Children Orchestrating Competing Voices in Multimodal, Digital Autobiographies. Issue 7 (July 2015) - Pandya, Jessica Zacher; Pagdilao, Kathleah Consul; Kim, Aeloch Enok; Marquez, Elizabeth
Background/Context: Prior research on multimodal, digital composition has highlighted the need for educators to bring such practices into classrooms, yet little research has been done to show what kinds of products children create and what those products can tell us as researchers about how children articulate their life experiences. We draw on recent theorizations of transnationalism in relation to immigrant children's school experiences, and Bakhtinian perspectives on language and ideology, to frame our analysis of the identity work that transnational and immigrant children undertook in the multimodal, digital composition projects we analyze. Purpose/Objective: We analyzed 18 digital videos made by transnational children aged 8–10, asking what the key features of their narratives told us about what they found important in their lives, what voices were orchestrated in the composition of those narratives, and what voices were omitted. We also asked what students' narratives told us about who they were and wanted to be, as immigrants or children of immigrants. Finally, we asked what these features and omissions suggested about perspectives on their immigration experiences and current lives. Research Design: These data come from an ongoing, design-based research project. Qualitative methods were employed, including: interviews with and surveys of children and teachers at various stages of the video production process; collection of children's written work; collection of children's videos; and the writing of field notes and analytic memos. Conclusions/Recommendations: Asking children to write about themselves for teachers, peers, and parents meant asking them to orchestrate multiple voices into potentially contradiction-ridden, yet coherent stories. Our work so far suggests that, at the least, we should expect children to try out new identities, and seek new ways of orchestrating the voices in their lives into a coherent whole. We caution researchers and teachers who work with immigrant youth not to assume that immigration will necessarily be a pivotal moment, or even a central or important moment, to children. We also caution that children may not feel that their school is a safe place to talk about such issues; offering the space is all we can do. The kinds of composition we have described exceed the narrative writing and speaking and listening demands of the Common Core State Standards. Teachers should be aware of the ways multimodal, digital composition can help meet their immigrant students' self-authoring needs and surpass the demands of the new standards. Finally, to connect with others, to become more aware of one's place(s) in an increasingly globalized world, and to orchestrate competing voices—these are the potentials for multimodal, digital composition with immigrant youth to which we continue to aspire.